Revision Rhinoplasty after Open Rhinoplasty: Lessons from 252 Cases and Analysis of Risk Factors. Issue 4 (October 2021) - Sibar, Serhat; Findikcioglu, Kemal; Pasinlioglu, Burak
Abstract : Background: In this study, patients who required aesthetic revision surgery after open rhinoplasty were retrospectively screened for risk factors. Methods: Two hundred fifty-two patients who underwent revision were included in the study. Nasal deformities before the revision were determined for each patient and evaluated in terms of their statistical relationship with preoperative nasal morphology and surgical techniques used. Results: The revision rate was found to be 10.8 percent. The three most common aesthetic reasons for revision were insufficient nasal tip rotation (37.7 percent), hanging columella (30.2 percent), and supratip deformity (28.6 percent). According to logistic regression analysis, the use of a strut increased the risk of inadequate nasal tip rotation by 5.3-fold compared to the tongue-in-groove technique, whereas inadequate nasal tip projection before surgery increased this risk by 2-fold. Being older than 40 years increased the risk of hanging columella by 6.8-fold, whereas the use of strut grafting instead of the tongue-in-groove technique increased this risk by 5.9-fold. The use of strut grafts instead of the tongue-in-groove technique increased the risk of supratip deformity by 2.2-fold. Conclusions: To ensure adequate nasal tip rotation after surgery in patients with advanced age and low nasal tip projection and rotation, it will be more appropriate to either use the tongue-in-groove technique or rotate the nasal tip more than normal. In patients with advanced age (>40 years) and low nasolabial angle before surgery, the use of tongue-in-groove technique instead of strut grafting may be advantageous for reducing the incidence of supratip and hanging columella. CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, III.